Therapeutic effect of a novel oxazolidinone, DA-7867, in BALB/c mice infected with Nocardia brasiliensis. - Lucio Vera-Cabrera; Alejandra Daw-Garza; Salvador Said-Fernández; Hector Gerardo Lozano-Garza; Noemi Waksman de Torres; Norma Cavazos Rocha; Jorge Ocampo-Candiani; Sung-Hak Choi; Oliverio Welsh (Public Library of Science (PLoS), 2008)
BACKGROUND: Mycetoma is a chronic infectious disease of tropical and subtropical countries. It is produced by true fungi and actinobacteria. In México, Nocardia brasiliensis is the main causative agent of mycetoma, producing about 86% of the cases; the gold standard for the therapy of mycetoma by N. brasiliensis is the use of sulfonamides which give a 70% cure rate. The addition of amikacin to this regime increases to 95% the cure rate; however, the patients have to be monitored for creatinine clearance and audiometry studies because of the potential development of side effects. Because of that it is important to search for new active compounds. In the present work, we evaluated the in vivo effect of DA-7867, an experimental oxazolidinone, on the development of experimental mycetomas by N. brasiliensis in BALB/c mice. METHODOLOGY/PRINCIPAL FINDINGS: In order to determine the optimal dose utilized to apply to the animals, we first determined by HPLC the plasma levels using several concentrations of the compounds. Based on these results, we used 10 and 25 mg/kg subcutaneously every 24 hr; DA-7867 was also supplied in the drinking water at a calculated dose of 25 mg/kg. As a control we utilized linezolid at 25 mg/kg, a compound active in murine and human infections, three times a day. The mice were infected in the right footpad with a young culture of N. brasiliensis HUJEG-1, and one week later we started the application of the antimicrobials for six more weeks. After that we compared the development of lesions in the groups injected with saline solution or with the antimicrobials; the results were analyzed by the variance ANOVA test. DA-7867 was able to reduce the production of lesions at 25 mg/kg, when given either subcutaneously or in the drinking water. CONCLUSIONS/SIGNIFICANCE: The experimental oxazolidinone DA-7867 is active in vivo against N. brasiliensis, which opens the possibility of using this drug once it is accepted for human application. Since oxazolidinones seem to be active against a wide spectrum of actinobacteria, it is possible they could be used in human cases of mycetoma by other actinomycetales, such as Streptomyces somaliensis, highly prevalent in Sudan, or Actinomadura madurae and A. pelletieri, which are commonly observed in Africa and India.